Cost analysis of management of cardiovascular disease comorbidities in Turkey. Issue 2 (3rd April 2019) - Koçkaya, Güvenç; Oğuzhan, Gülpembe Ergin; Özin, Bülent; Yılmaz, Kerem Can; Çiftçi, Orçun; Çavuş, Filiz; Sharaf, Amir Mustapha; Buyuktuna, Nazım; Buyukısık, Tansu; Saylan, Mete
Abstract: Objectives: The strongest muscle of human body, the heart, is susceptible to a range of diseases. These diseases involve deterioration of the blood vessels, muscles of heart, malformation of cardiovascular structures, tumour formations, formation of clots, rupturing of vessels and others. Therefore, taking into consideration the direct and indirect burdens of cardiovascular diseases around the globe, the present study was designed to perform a direct cost analysis of managing comorbidities of cardiovascular diseases with reimbursement authority perspective. Methods: The cost analysis study conducted in the present article was conducted in three phases. The first phase involved filling of survey questionnaire by five experts practicing in the field of cardiology in Turkey. The second phase comprised of expert panel wherein three out of five experts reviewed the forms filled by all the experts. This was followed by third phase wherein the three experts attending the panel re-filled the questionnaire as per the daily clinical practice. Key Findings: The findings showed total annual costs for cardiovascular diseases (CVDs) exhibiting myocardial infarction comorbidities for both acute and maintenance treatment as 5622.95 and 1245.04 TL respectively. The total costs for major bleeding events were found to be 1211.95 TL, whereas for minor bleeding events the costs were 496.26 TL. The total cost for intracranial bleeding was 1761.53, and 3595.62 TL for stroke, which followed myocardial infarction. Conclusion: The study findings helped gain an insight into the most prominent comorbidities associated with CVDs in the perspective of reimbursement institution including direct costs. Further studies are needed to understand the real cost for reimbursement institution.